Establishing Bandung as a Center of Nationalism: R. A. A. Wiranatakusumah V's Political Policies Amidst the Independence Movement - Savitri, Alfa Dini; Hidayat, Asep Achmad; Supendi, Usman (TEMALI : Jurnal Pembangunan Sosial, 2024)
This study aims to analyze the political policies of R.A.A. Wiranatakusumah V in establishing Bandung as a center of nationalism amidst Indonesia's independence movement. This research uses a literature study method with a historical approach to explore Wiranatakusumah V's role as the Regent of Bandung, including his response to significant events such as the founding of the Indonesian National Party (PNI) and Bung Karno's trial by the Dutch Colonial Landraad. The findings indicate that R.A.A. Wiranatakusumah V's policies successfully made Bandung a region that welcomed the national movement while maintaining harmony between indigenous and colonial groups. This research contributes to a deeper understanding of how inclusive and nationalist political policies can shape a city's identity as a center of the national movement. The study also offers lessons for the younger generation on the importance of leadership that can unite various societal elements in the struggle for independence.